Psycho-oncology practice for cancer patients during the pandemic lockdown in Italy: A qualitative mixed-method study with psychotherapists - Luca Ghirotto; Ludovica De Panfilis; Marta Perin; Alessandra Miraglia Raineri; Francesco De Vincenzo; Matías Eduardo Díaz Crescitelli; Elisa Rabitti; Silvia Di Leo (PLoS ONE, 2025)
Background At the beginning of the COVID-19 outbreak, psychotherapy practice underwent a drastic reorganization. To enhance knowledge of the challenges healthcare professionals faced during the pandemic, this study explores the experiences and practices of Italian psychotherapists caring for cancer patients during the first phase of the COVID-19 pandemic. Method This mixed-method study consists of a qualitative cross-sectional survey followed by open-ended semi-structured interviews with a subsample of survey respondents. The data were then triangulated to depict better the experience of caring for cancer patients from the psychotherapists’ perspective. Results The final dataset included 102 valid responses. Subsequently, one male and 21 females participated in the interview-based study. Qualitative analysis revealed four themes and specific subthemes: 1. patient relationships (the impact of restrictions on family ties, the impact of restrictions within the healthcare environment), 2. clinical practice management (the use of technologies for psychological interventions, timing and continuity of care, changes in the number of requests for psychological interventions), 3. emotional aspects (emotions captured in patients, emotions captured in other professionals, the inner world of the psychotherapists), and 4. organizational recognition (investments in psychological support and service coordination, issues related to employment status). Conclusion Our findings provide knowledge of the pandemic’s impact on psycho-oncology practice, offering further input for research on innovative tools in psychotherapy and staff support programs and the development of psycho-oncology services that can systematically respond to the multifaceted needs of cancer patients, relatives, and healthcare professionals.